Response of groundwater levels to ENSO under the influence of mining - Zhou, Xiaoping; He, Shifang; Sang, Honghui; Ge, Weiya (Frontiers in Earth Science, 2025)
Human activity and climate change have significantly modified the hydrological processes of groundwater. In coal mining areas, dewatering operations have become more influential than climate change, making human activity the primary factor impacting groundwater systems. However, it remains unclear to what extent climate change affects groundwater levels under such strong human influence. This research examines the impact of El Niño Southern Oscillation (ENSO) on groundwater levels, using data from the Pansan Coal Mine in Huainan, China as a case study. We employ wavelet analysis to study four groundwater level time series and investigate the impacts of ENSO and precipitation. The study results indicate that, in cases of groundwater over-exploitation, significant regions in the Continuous Wavelet Transform of groundwater levels decrease significantly. However, despite the substantial drops in groundwater levels caused by mining activities, a distinct resonance period with precipitation and ENSO remains evident in the Cross Wavelet Transform. Human activities have not altered the resonance frequencies between groundwater levels and either precipitation or ENSO. Precipitation correlates with porous groundwater levels on an annual scale and with karst groundwater levels on both annual and inter-annual scales. ENSO significantly impacts Quaternary groundwater levels on annual and inter-annual scales, and it affects Neogene and karst groundwater levels on inter-annual scales. Conducting-water structures serve as the primary pathways for transmitting precipitation and ENSO signals. The findings and methodologies presented in this study can help managers and scientists in enhancing groundwater resource management, sustainable utilization and water disaster prevention amid future climate uncertainties.